Down-Regulation of Nucleolar and Spindle-Associated Protein 1 (NUSAP1) Expression Suppresses Tumor and Cell Proliferation and Enhances Anti-Tumor Effect of Paclitaxel in Oral Squamous Cell Carcinoma. - Atsushi Okamoto; Morihiro Higo; Masashi Shiiba; Dai Nakashima; Tomoyoshi Koyama; Isao Miyamoto; Hiroki Kasama; Atsushi Kasamatsu; Katsunori Ogawara; Hidetaka Yokoe; Hideki Tanzawa; Katsuhiro Uzawa (PLoS ONE, 2015)
Nucleolar and spindle-associated protein 1 (NUSAP1) is an important mitotic regulator. In addition to its crucial function in mitosis, NUSAP1 has recently received attention due to the interesting roles in carcinogenesis. The aim of this study was to reveal functional mechanisms of NUSAP1 in oral squamous cell carcinoma (OSCC).mRNA and protein expression levels of NUSAP1 in 9 OSCC-derived cells were analyzed by quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) and immunoblotting analyses. The correlation between the NUSAP1 expression profile and the clinicopathological factors was evaluated by immunohistochemistry (IHC) in clinical OSCC samples (n = 70). The NUSAP1 knockdown cells were established with short hairpin RNA (shRNA) in OSCC cells, and functional assays were performed using these cells. In addition to the evaluation of cellular proliferation and cell cycle, we also investigated the potential role of NUSAP1 in paclitaxel (PTX)-induced cellular responses.mRNA and protein expression of NUSAP1 were significantly up-regulated in OSCC-derived cells compared with human normal oral keratinocytes (P < 0.05). IHC revealed that NUSAP-1 expression is closely associated with primary advanced T stage (P<0.05). Suppression of NUSAP1 expression levels led to significant (P < 0.05) inhibition of cellular proliferation. Furthermore, apoptosis induced by PTX was enhanced in NUSAP1 knockdown OSCC cells.NUSAP1 may be a crucial biomarker for OSCC. Moreover, down-regulated NUSAP1 expression suppresses tumor proliferation and also enhances anti-tumor effect of PTX by activating apoptotic pathways. Thus, the present study strongly suggests that regulating NUSAP1 expression should contribute to the therapy for OSCC.